Pioglitazone enhances cisplatin's impact on triple-negative breast cancer: Role of PPARγ in cell apoptosis - Qamraa Hamad Alqahtani; Layla Abdullah Alkharashi; Hanaa Alajami; Ishraq Alkharashi; Layan Alkharashi; Shoug Nasser Alhinti (Elsevier, 2024)
Peroxisome proliferator-activated receptor-gamma (PPARγ) has been recently shown to play a role in many cancers. The breast tissue of triple-negative breast cancer (TNBC) patients were found to have a significantly lower expression of PPARγ than the other subtypes. Furthermore, PPARγ activation was found to exert anti-tumor effects by inhibiting cell proliferation, differentiation, cell growth, cell cycle, and inducing apoptosis. To start with, we performed a bioinformatic analysis of data from OncoDB, which showed a lower expression pattern of PPARγ in different cancer types. In addition, high expression of PPARγ was associated with better breast cancer patient survival. Therefore, we tested the impact of pioglitazone, a PPARγ ligand, on the cytotoxic activity of cisplatin in the TNBC cell line. MDA-MB-231 cells were treated with either cisplatin (40 μM) with or without pioglitazone (30 or 60 μM) for 72 h. The MTT results showed a significant dose-dependent decrease in cell viability as a result of using cisplatin and pioglitazone combination compared with cisplatin alone. In addition, the protein expression of Bcl-2, a known antiapoptotic marker, decreased in the cells treated with cisplatin and pioglitazone combination at doses of 40 and 30 μM, respectively. On the other hand, cleaved- poly-ADP ribose polymerase (PARP) and -caspase-9, which are known as pro-apoptotic markers, were upregulated in the combination group compared with the solo treatments. Taken together, the addition of pioglitazone to cisplatin further reduced the viability of MDA-MB-231 cells and enhanced apoptosis compared with chemotherapy alone.